“A Humanised Nature and a Naturalised Humanity” Thinking with Gramsci on the Relationship between Man and Nature - Coletto, Simone (International Gramsci Journal, 2024)
Starting from the problem of the «objective reality of the external world» and Gramsci’s critique of Bukharin’s naive materialism, this paper discusses the relationship between human beings and nature. While ontological materialism conceives of nature independently of its relation to humanity, Marxism emphasises this dialectical connection. In this way, materialism is transformed into a practical, i.e., historical and social, materialism. Epistemological reflection thus moves onto the political terrain: it becomes a reflection on the possibilities of transforming reality and building a society in which both the opposition between man and nature and between man and man are finally resolved.